Estudo randomizado e duplo-cego sobre o efeito do uso de gel não hormonal na região vulvar em mulheres menopausadas com disfunção sexual - Salmeron, Camilla Correia Parente [UNIFESP] (2020)
INTRODUCTION: The menopausal transition consists of anatomical, physiological and psychological changes that often have negative effects on female sexuality3. The onset of climacteric is accompanied by a progressive increase in the reported symptoms of: vaginal dryness, urinary incontinence, recurrent urinary infections, pain, irritation, itching, dyspareunia and bleeding after sexual intercourse1. OBJECTIVE: Randomized, double-blind study aimed at evaluating the effects of a non-hormonal moisturizing vulvar gel containing visnadine, ethil ximeninate, coleus barbatus and panicum miliaceum (TROFIS ®), in postmenopausal women, regarding the response measurement measured by the FSFI sexual function index compared to placebo. METHODS: Thirty menopausal patients were selected, with active sexual life and fixed partner, complaining of hypoactive sexual desire. Patients were randomized in a double-blind study divided into placebo and intervention groups. Randomization was performed in a 1: 1 ratio. A non-hormonal gel was used, with a moisturizing proposal, containing Visnadine, Ethylximenate, Coleus barbatus and Panicum miliaceum and the control only with the vehicle (the same used in the group with the active drugs. Patients were instructed to use a daily small amount of the gel provided in consultation, at any time of the day, unrelated to sexual intercourse for 30 (thirty) days. The participants were evaluated according to the response to the FSFI questionnaire (Index of Female Sexual Function), at the initial moment, before the use of the gel, and after 30 days of use RESULTS: In all FSFI measurements, we observed a lack of statistical significance comparing the active intervention versus the placebo group (p-values ​​<0.05), controlling for age and line measurements CONCLUSION: It was not possible to observe statistically significant differences when comparing the two groups.The clinical approach of sexual complaints in the menopausal and postpartum transition period Menopause should be performed routinely, understanding the impact of this condition on the quality of life of patients. Further studies are needed to define options for approach and treatment of this complaint.